AiU which is temporarily ceasing ops will continue sponsoring students - Sunday, Star (Sunday Star, 2014)
PETALING JAYA: Students from Albukhary International University (AiU), which is temporarily ceasing operations, will continue to be sponsored by the Albukhary Foundation.